Remaja Tanpa Anemia Dalam Rangka Pembentukan SDM Unggul : Social Approach - Sukmana, Dhika Juliana; Noamperani, Sapta Rahayu; Farahdiba, Regina Karima Putri; Nurmadani, Farisa Zahra; Jannah, Auliya Miftakhul (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
Teenagers are one of the assets owned by a nation and will become the nation's next generation. To optimize the demographic bonus, it is necessary to prepare as well as possible, one of which is by providing outreach regarding anemia. Anemia is known to be an aspect that affects development, especially in women. This outreach is aimed at increasing knowledge related to anemia. This activity is carried out by providing counseling or outreach through leaflets and material handbooks. The results of this activity can increase the participants' knowledge. This increase can be seen from the pretest and posttest scores.